Dendritic Cells Attenuate the Early Establishment of Endometriosis-Like Lesions in a Murine Model. (October 2014) - Stanic, Aleksandar K.; Kim, Minji; Styer, Aaron K.; Rueda, Bo R.
Complex interplay of innate and adaptive immune cells has been implicated in the establishment, maintenance, and progression of endometriosis. Defining the identity, activation state, and functional role of immune cells during lesion establishment will provide invaluable insight into the underlying mechanisms of disease. This study utilized a transgenic mouse model with conditional dendritic cell (DC) depletion (diphtheria toxin-treated B6.FVB-Itgax-hDTR-EGFP tg ) and multiparametric flow cytometry to examine immune cell composition and activation state and to assess the functional role of DCs in endometriosis-like lesions. T cells and DCs were increased in lesions compared to native uteri and control splenocytes and demonstrated an activated phenotype ( P < .05). Lesions in DC-depleted hosts demonstrated greater size ( P < .001) and reduced expression of T-cell activation marker CD69 compared to controls ( P < .05). Collectively, these results suggest that activated DCs within lesions activate T cells and result in the impairment of early lesion establishment.